Does Convenience Come with a Price? The Impact of Remote Testimony on Perceptions of Expert Credibility - Jones, Ashley C. T. (Criminal justice and behavior, 2023)
The purpose of the present study was to experimentally examine whether testimony modality leads to differences in perceptions of expert witnesses and their opinions. We hypothesized that simulated testimony delivered via phone would be perceived as less credible, efficacious, and assigned less weight than testimony delivered via videoconference or in-court. We recruited a sample of 275 U.S. men and women via Amazon Mechanical Turk. After viewing a videotaped mock court scenario depicting testimony by a forensic psychological expert witness, participants completed measures of expert credibility, efficacy, and expert social presence. A simple contrast multivariate analysis of variance (MANOVA) revealed perceptions did not differ between in-court, videoconferencing, and phone testimony conditions. Higher social presence scores predicted more favorable perceptions of the expert. These findings provide clearer support for the continued implementation of remote videoconference testimony in courts. We offer recommendations on how to optimize the use of remote testimony based on the present study and previous findings.